2015
DOI: 10.1002/anie.201500250
|View full text |Cite
|
Sign up to set email alerts
|

A Bioorthogonal Chemical Reporter of Viral Infection

Abstract: Pathogen-selective labeling was achieved by using the novel gemcitabine metabolite analogue 2'-deoxy-2',2'-difluoro-5-ethynyluridine (dF-EdU) and click chemistry. Cells infected with Herpes Simplex Virus-1 (HSV-1), but not uninfected cells, exhibit nuclear staining upon the addition of dF-EdU and a fluorescent azide. The incorporation of the dF-EdU into DNA depends on its phosphorylation by a herpes virus thymidine kinase (TK). Crystallographic analyses revealed how dF-EdU is well accommodated in the active si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 51 publications
(23 reference statements)
2
32
0
Order By: Relevance
“…This compound was efficiently incorporated into DNA by HeLa cells when the cells were transformed to express a low‐fidelity thymidine kinase‐1 from Herpes simplex virus‐1. In contrast, wild‐type HeLa cells exhibited little or no metabolic incorporation of AmdU into DNA, due to the relatively high fidelity of human thymidine kinases . These results are consistent with previous studies that demonstrated that the initial phosphorylation of certain nucleosides can be the limiting step for enzymatic production of nucleotide triphosphates .…”
Section: Methodssupporting
confidence: 90%
“…This compound was efficiently incorporated into DNA by HeLa cells when the cells were transformed to express a low‐fidelity thymidine kinase‐1 from Herpes simplex virus‐1. In contrast, wild‐type HeLa cells exhibited little or no metabolic incorporation of AmdU into DNA, due to the relatively high fidelity of human thymidine kinases . These results are consistent with previous studies that demonstrated that the initial phosphorylation of certain nucleosides can be the limiting step for enzymatic production of nucleotide triphosphates .…”
Section: Methodssupporting
confidence: 90%
“…Modified nucleosides have thus far been critical toward understanding the rate of RNA synthesis and turnover, [3] characterizing the RNA-binding proteome, [16] and even tracking viral infection. [17] As such, our azide-modified nucleosides are poised to expand the arsenal of methods used to analyze RNA in cells as well as in complex environments such as tissues and living animals.…”
mentioning
confidence: 99%
“…The alkyne group of EdU plays an important role as a chemical handle for reaction with an azide‐functionalized fluorophore using click chemistry, allowing detection of the DNA by high‐content imaging. A small number of nucleoside chemical probes structurally related to EdU have been synthesized and used in varying capacities as chemical probes for DNA (Neef & Luedtke, ; Neef, Pernot, Schreier, Scapozza, & Luedtke, ; Neef, Samain, & Luedtke, ). The only difference between 2ʹ‐fluoro‐arabinosyl EdU (F‐ara‐EdU) and EdU is in the 2ʹ position.…”
Section: Introductionmentioning
confidence: 99%